Nutrient status of rangeland in upper Mustang - Maharjan, M.; Awasthi, K. D.; Pande, K. R.; Thapa, N. (Banko Janakari, 2015)
The study aimed at assessing the nutrient status of rangeland in upper Mustang. The assessment is necessary to know about the soil quality or productivity of soil of rangeland. Livestock rearing is one of the main occupations in upper Mustang but nowadays due to lack of palatable species for livestock, people are leaving the occupation which is directly affecting their livelihood status. Therefore this research was carried out to find out if the soil nutrient is the reason behind the lack of availability of palatable species in the rangeland. For soil sampling, north and south aspects were taken. In case of altitude, 3850 m, 3650 m and 3450 m were taken. Soil samples were taken from soil profile up to 60cm depth at interval of 20 cm. Available phosphorus and available potassium were found to be high at north aspect but total nitrogen was found to be high at south aspect. Both total nitrogen and available phosphorus were found to be high at 3650 m. Available potassium was gradually decreased with increasing altitude. Total nitrogen, available potassium and available phosphorus were gradually decreased with increasing soil depth. Nutrient status was high at top soil (0-20 cm).The soil nutrient (Nitrogen, Phosphorus, Potassium) status was found to be good in the study area. Further research on biophysical and ecological aspect of Rangeland in Upper Mustang is necessary to manage it properly. Banko Janakari, Vol. 24, No. 1, PP. 41-46